2016
DOI: 10.1016/j.coal.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation on temperature, chemistry and isotopes of mine water pumped in Bytom geological basin (USCB Poland) as a potential geothermal energy source

Abstract: Preliminary investigation on temperature, chemistry and isotopes of mine water pumped in Bytom geological basin (USCB,Southern Poland) as a potential geothermal energy source. International Journal of Coal Geology, 164, pp. 104-114. (doi:10.1016/j.coal.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. AbstractMine water from both operating and abandoned mines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Stable isotope analyses were undertaken at the Scottish Universities Environmental Research Centre (SUERC) laboratories, East Kilbride, and full details of procedure can be found in Burnside et al (2016). Samples of water for δ 18 O and δ 2 H were taken in triplicate using clean 10 ml screwcap glass vials sealed with Parafilm to prevent any evaporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotope analyses were undertaken at the Scottish Universities Environmental Research Centre (SUERC) laboratories, East Kilbride, and full details of procedure can be found in Burnside et al (2016). Samples of water for δ 18 O and δ 2 H were taken in triplicate using clean 10 ml screwcap glass vials sealed with Parafilm to prevent any evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, water quality variations can be related to depth and to effects of the exploitation method (mixing induced by pumping, effect of reinjection, pumping at different depths, etc.). Detailed hydrogeochemical studies of pumped mine waters in the UK (Burnside et al 2016a and b) and Poland (Janson et al 2016) have revealed much about the history and subsurface mixing of mine waters, provided vital information for geothermal projects, and have laid the foundations for further mine water geothermal investigations, such as this one.…”
Section: Introductionmentioning
confidence: 99%
“…Less mineralized groundwater percolates into the mine from shallower aquifers and fills the water column at the top, while more mineralized mine water usually can be found in deeper sections of the mine. Convective cells of different water qualities, driven for example by thermal gradients, may also build up in the subsurface controlled by the mine structure, such as developed roadways (Burnside et al 2016a, b;Janson et al 2016;Hünefeld-Mugova and Wolkersdorfer 2018). Disturbances of the system's hydraulic equilibrium can result in a collapse of the water body's stratification and the uncontrolled discharge of contaminated mine water.…”
Section: Introductionmentioning
confidence: 99%
“…The work reported in this paper specifically addresses the design and operation of heat exchange solutions to understand and minimise hydrogeochemical risks. Internationally, the Barredo shaft heat pump scheme at Mieres, northern Spain (Loredo et al 2017), and the proposed Ewa shaft heat pump scheme at the Szombierki coal mine, Bytom, Poland (Janson et al 2016), are included as LoCAL study sites, together with a number of schemes in the United Kingdom. The paper will examine, in turn, the British LoCAL study sites and summarise the experiences to date with each site.…”
Section: Introduction: Mine Water As a Thermal Resourcementioning
confidence: 99%